A critical analysis of 'received by or accrued to' as contemplated in the 'gross income' definition in section 1 of the Income Tax Act with reference to the Consumer Protection Act. Issue 3 (2nd September 2017) - Thiart, C
Abstract : The introduction of the Consumer Protection Act 68 of 2008 has had significant implications for the South African commercial arena. This Act forms part of government regulation and is aimed at protecting the rights of consumers. Not only does the Consumer Protection Act 68 of 2008 have a significant impact on the manner in which parties conduct business; it also affects the accounting and taxation treatment of amounts that fall within the scope of the Act. This article investigated the effect of the provisions contained in section 62 to section 65 of the Consumer Protection Act 68 of 2008 on the tax implications of certain amounts. These amounts include lay-bys, prepaid certificates, credits, vouchers and deposits (prepaid amounts). Particular attention was given to the meaning of receipts and accruals within the definition of gross income in section 1 of the Income Tax Act 58 of 1962, and the effect of section 62 to section 65 of the Consumer Protection Act 68 of 2008 on this Act. A literature review of the relevant legislation, terms used therein, and further applicable literature was undertaken. The study concluded with three recommendations in order to align the different items of legislation. The first is to extend section 65 of the Consumer Protection Act 68 of 2008 to include the requirements that must be met to prove that a supplier adheres to the fiduciary duty imposed on it by the Consumer Protection Act 68 of 2008. The South African Revenue Service must consider an amendment to the gross income definition, or specific legislation to this effect. Alternatively, the South African Revenue Service must provide the supplier with its view on and interpretation of section 62 to section 65 of the Consumer Protection Act 68 of 2008 and the applicability thereof on the definition of gross income, as contained in section 1 of the Income Tax Act 58 of 1962.